(untitled) (Mongolian Journal of International Affairs, 2022)
This study has focused on border regions relations and cooperation between the Mongolia and Buryatia. As a border region, Buryatia has a centuries-old history of economic, political, cultural and humanitarian relations with Mongolia. Our relations have been successfully developing in all areas, high-level reciprocal visits have become regular, and mutual trust has been expanding.